Spatialization of mortality from mental and behavioral disorders attributable to the use of psychoactive substances in Brazil, from 2010 to 2016 - Marques, Marilane Vilela; Silva, Jadna Kelly da; Galvão Moura, Lillian Batista Palhano; Almeida, Harinson Carpegeano Câmara de; Filho, Alcebíades de Sousa; Amador, Ana Edimilda (HSJ, 2020)
Introduction: Mental and behavioral disorders attributable to the use of psychoactive substances constitute an important public health problem, due to their prevalence and the risk of promoting disability and death. Objective: To analyze the spatial distribution of mortality from mental and behavioral disorders attributable to the use of psychoactive substances in Brazil. Methods: Ecological study in municipalities in Brazil, from 2012 to 2016. Spatial distribution, intensity and significance were analyzed using the Moran Global, MoranMap and BoxMap index. Results: Most deaths were attributable to the use of alcohol (n = 33,177; 77.36%), followed by smoking (n = 7,262; 16%) and the use of multiple drugs (n = 1,409; 3.29%), with the majority (n = 36,861; 85.97%) being male and 46.31% single. In the age groups between 40 and 59 years, there were 21,712 deaths (50.63%), and between 60 and over, 13,445 deaths (31.35%). The municipalities with the highest standardized average mortality rates (deaths / 100 thousand inhabitant) were: Charrua – RS (43.60), Uru – SP (43.19), Riacho da Cruz – RN (42.21), Senhora do Porto – MG (42.19), Mata – RS (36.81), Pendências – RN (35.26) and Catuji – MG (35.19). The value of the Global Moran Index was 0.216 (p = 0.01). At MoranMap, a high/high cluster formation was observed in the Northeast and Southeast regions. Conclusion: In Brazil, there is a pattern of spatial dependence on the distribution of mortality attributable to the use of psychoactive substances.